Representations of “female Asian look” in Advertising : Young Chinese Women’s Responses to Fashion and Beauty Advertisements Targeting Chinese Market - Rong, Haoyi (2020)
This study was inspired by two advertisement series targeting the Chinese market, Dolce&Gabbana’s “Eating with chopsticks” campaign videos, and Zara’s makeup posters of a new released lipstick series. Having these two advertisements as cases, this study used focus group interview to collect data of young Chinese women responding to these advertisements and used Critical Discursive Psychology (CDP) to analyze the interview data. This study draws on the three main concepts of CDP: interpretive repertoire, ideological dilemma, and subject position, to find out what kind of repertoires surrounding the “female Asian look” in both advertisements are possible to emerge, and how are the opinions and repertoires socially constructed. Findings of this study suggest that young Chinese women’s responses to “female Asian look” in both cases were mainly constructed in reading through social media comments, interacting with others, and other social and cultural norms such as Chinese beauty standards and their general impression of western brands. Visible dilemmas, contradictory repertoires and different subject positions were observed and discussed in the responses. Findings of this study could also be helpful for future companies wishing to enter the Chinese market.